Numerical evaluation of the corrosion effects in prestressed concrete beams without shear reinforcement. (9th January 2020) - Belletti, Beatrice; Vecchi, Francesca; Bandini, Cecilia; Andrade, Carmen; Montero, Javier Sánchez
Abstract: Corrosion of prestressed concrete structures causes size reduction of strands, degradation of mechanical properties of steel, cracking of the surrounding concrete, and bond decay at steel‐to‐concrete interface. In this paper, a numerical approach able to take into account all the effects involved in the corrosion process by using nonlinear finite element analysis (NLFEA) and membrane or shell elements modeling is proposed. Two different strategies are adopted to model strands: the smeared and the discrete approaches. The results obtained using these latter strategies are validated by comparing NLFEA results with experimental measurements of a naturally corroded prestressed beam tested at the "Instituto de Ciencias de la Construcción Eduardo Torroja" in Madrid. Finally, pros and cons of the proposed modeling approach are critically analyzed, demonstrating that considering the actual spatial corrosion distribution is necessary to predict the position where failure occurs.